Implications of Managerial Talent Projections for Management Education - Miner, John B. (Academy of Management Review, 1977)
Declining motivation to manage among college students poses the threat of severe managerial talent shortages. Socially responsible business education must move to meet this challenge by adding programs in managing (not just management) to existing curricula. Managerial role-motivation training is essential to any such program.